2007
DOI: 10.3201/eid1311.070506
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Predictors of Human West Nile Virus Infections, Colorado

Abstract: To determine whether environmental surveillance of West Nile virus–positive dead birds, mosquito pools, equines, and sentinel chickens helped predict human cases in metropolitan Denver, Colorado, during 2003, we analyzed human surveillance data and environmental data. Birds successfully predicted the highest proportion of human cases, followed by mosquito pools, and equines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
37
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 11 publications
2
37
1
1
Order By: Relevance
“…A large number of mosquito pools means an increased vector population, hence a high prevalence of WNV and an increased risk of West Nile infection in humans. This is consistent with the findings of Patnaik et al [6] that mosquito pools were significant in predicting WNV prevalence in Colorado. These results are robust to a variety of model specifications.…”
Section: Discussionsupporting
confidence: 93%
“…A large number of mosquito pools means an increased vector population, hence a high prevalence of WNV and an increased risk of West Nile infection in humans. This is consistent with the findings of Patnaik et al [6] that mosquito pools were significant in predicting WNV prevalence in Colorado. These results are robust to a variety of model specifications.…”
Section: Discussionsupporting
confidence: 93%
“…Each surveillance method provides unique information about viral activity in the vector and host populations; dead birds inform control agencies about the location and magnitude of virus activity, testing of Our results for the timeliness of detection showed that mosquitoes and dead birds generally detected virus activity earlier than nearby sentinel chicken flocks when sampling frequency and spatial density were equalized. Our findings agree with those of several studies, which showed infection in mosquitoes and WNV-positive dead birds preceded sentinel chicken seroconversion by 1-2 weeks (Cherry et al 2001, Patnaik et al 2007, Unlu et al 2009, Kwan et al 2010. Part of this lag in detection by sentinel chickens may be due to the delay between the infectious mosquito bite and the time when antibodies become detectable by ELISA in the sentinel chickens, which can be 7-10 days after the infectious bite (Senne et al 2000, Patiris et al 2008.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies of existing surveillance programs have found that surveillance for WNV-positive mosquitoes and/or dead birds preceded WNV seroconversions in sentinel chickens and were more predictive of WNV disease risk in humans (Cherry et al 2001, Patnaik et al 2007, Unlu et al 2009, Kwan et al 2010). However, those comparisons did not account for differences in sampling effort or costs required for each method.…”
Section: Introductionmentioning
confidence: 96%
“…Previous analyses have indicated that sentinel chicken seroconversions were delayed relative to mosquito or dead bird infection data and therefore were not useful as an early warning of WNV transmission to humans. [11][12][13][14][15][16] Similar studies have been contradictory, indicating that sentinel chickens were useful for WNV and other flavivirus surveillance applications. [17][18][19][20][21][22][23] These conflicting results have led to divergence in opinion over the use of sentinel chicken data for risk assessment.…”
Section: Introductionmentioning
confidence: 99%